NEUROIMMUNOLOGICAL ASPECTS OF PATHOGENESIS IN CHILDREN’S CEREBRAL PALSY - L. Z. Gaysina; D. D. Gaynetdinova; R. F. Khakimova (Медицинская иммунология, 2014)
Аbstract. Present review article considers neuroimmunological issues in pathogenesis of infantile cerebral paralysis  (ICP).  Various  factors  of  immune  system  and  cytokine  regulation  network  (including  TNFα, interleukins) have been shown to participate in development of pathological events in patients with periventricular leukomalacia which result into evolving ICP. Selective cytotoxic activity of TNFα was analyzed as a factor in development of continuous chronic process. A role of immunopathological events for development of cytogenetic rearrangements in peripheral blood cells is proposed. (Med. Immunol., 2011, vol. 13, N 2-3, pp 115-120)